(untitled) (Plant Tissue Culture and Biotechnology, 2025)
This study established an efficient in vitro seed germination and seedling development protocol for large-scale seedling production of Acampe rigida. Seed germination was highest on half strength MS medium (91.67%), followed by MS with 10% coconut water (83.33%), while lower rates were recorded on full strength MS medium (75%), Vacin and Went (VW) medium (58.33%) and Knudson’s C (KC) medium (41.67%). Half-strength MS medium also showed the shortest time requirements for seed germination (17-22 days), protocorm-like body (PLB) development (30-35 days) and first leaf primordia differentiation (47-52 days). Compared to MS and ½MS, VW medium was suitable for the further development of protocorms. Protocorms exhibited 100% survival and seedling differentiation, with a maximum seedling length of 2.59 ± 0.10 cm in VW medium containing 10% coconut water and 10 g/l banana homogenate. Hormone-free VW medium with 10 g/l banana homogenate and 0.1% activated charcoal provides optimal growth and development of in vitro germinated seedlings. Healthy seedlings exhibited 80% survivability on a potting mixture of coconut husk, tree bark, charcoal and moss (2 : 1 : 1 : 1). Plant Tissue Cult. & Biotech. 35(1): 41-49, 2025 (June)